2009
DOI: 10.3174/ajnr.a1616
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Aqueductal CSF Stroke Volume in Shunted Patients with Idiopathic Normal-Pressure Hydrocephalus

Abstract: BACKGROUND AND PURPOSE:Aqueductal CSF stroke volume (ACSV) measured by phase-contrast MR imaging is a tool for selection of surgical patients with idiopathic normal-pressure hydrocephalus (iNPH). The aim of the present study was to investigate whether there is a relationship between clinical outcome and changes in ACSV in patients with iNPH who have been shunted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 18 publications
6
33
1
4
Order By: Relevance
“…As pointed out by Chiang et al, 33 it seems reasonable that the aqueduct can adapt to increased flow, similar to the ad- aptation of the blood vessel lumen area to maintain a wall shear stress within a normal range. 37 ASV and ventricular volume declined after shunting; this change is consistent with that in previous studies, 14,38 while aqueductal area did not change. While ASV did not reflect the clinical severity of iNPH preshunting and did not compare with any pressure parameters, reduced ASV after shunting might therefore be primarily influenced by reduced ventricular size, rather than reflecting a clinical response, contrary to what has been suggested previously.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As pointed out by Chiang et al, 33 it seems reasonable that the aqueduct can adapt to increased flow, similar to the ad- aptation of the blood vessel lumen area to maintain a wall shear stress within a normal range. 37 ASV and ventricular volume declined after shunting; this change is consistent with that in previous studies, 14,38 while aqueductal area did not change. While ASV did not reflect the clinical severity of iNPH preshunting and did not compare with any pressure parameters, reduced ASV after shunting might therefore be primarily influenced by reduced ventricular size, rather than reflecting a clinical response, contrary to what has been suggested previously.…”
Section: Discussionsupporting
confidence: 81%
“…After Bradley et al 6 first reported an increased CSF flow void in the aqueduct associated with a favorable shunt response, studies using phase-contrast MR imaging (PCMR) have demonstrated aqueductal flow parameters, and in particular the aqueductal stroke volume (ASV), to be useful in the diagnosis and selection of patients for shunt surgery [7][8][9][10][11][12][13] and in the follow-up of patients with shunts. 14 However, other studies do not reproduce the beneficial utility of measuring aqueductal flow [15][16][17][18] ; therefore, the use of ASV in iNPH remains disputed. Accordingly, comparisons with invasive intracranial measurements are warranted.…”
mentioning
confidence: 99%
“…[21][22][23] PVI CC together with ⌬V CC determines the impact on the brain caused by the arterial pulsations (approximately 30 million each year). With increasing age, arterial physiology changes.…”
Section: Discussionmentioning
confidence: 99%
“…It is controversial whether the above imaging diagnosis predicts the shunt response, 23,24,32,41,72) but measurements of the preoperative peak flow velocity of CSF 103,122) and stroke volume, reflecting the CSF volume following the cerebral aqueduct, 6,120,121) have been reported to be clinically useful predictors of the shunt response, and these may be considered for preoperative examinations; however, the measurement methods have not been standardized and their diagnostic value has not been established. Reduced venous circulation in the sagittal and straight sinuses and intracranial compliance on heart rate-gated phase-contrast MRI have been reported, 11,12) but their diagnostic values have not been established.…”
Section: -A-iii Csf Flow Void By Mri and Csf Flow Rate By Phase-conmentioning
confidence: 99%